دورُ التكتلات الإقتصاديَّة الدوليَّة في تغيير بنيَّة النظامِ الدّولي "البريكس" انموذجاً - المصري خالد; علوش مناف (Latakia University Journal - Economic and Legal Sciences Series, 2017)
أشارت سلسة الأحداث الدوليَّة الأخيرة في العالم إلى أنَّ العلاقات الدوليّة تشهد اضطراباً كبيراً، وكشفت هذه الأحداث والتطورات أنَّ النظام الدولي الأحادي القطبيَّةً والذي عرفه العالم منذ انهيار الاتحاد السوفيتي، دخل فترة تغيرات سياسيَّة غامضة، وخاصة بعد الأزمة الماليه العالميَّة 2008. وأظهرت هذه التطورات والتغيرات في المجالات السياسيَّة والاقتصاديَّة والعسكريَّة إلى بروز قوى على المستوى العالمي ممثلة التكتلات الإقتصاديَّة الدوليه تحاول التأثير في الدائرة الأولى من النظام الدولي وذلك عن طريق خلق توازن دولي جديد ومن هذه التكتلات التي ظهرت على الساحة الدوليَّة هي تكتل البريكس. إنَّ الجدل في أدبيات العلاقات الدوليَّة حول أثر بنيَّة النظام الدولي في سلوك الوحدات الفاعلة فيه سواء كانت دولاً أم نظماً فرعيَّة والآن قوى فاعلة غير الدولة مثل التكتلات الإقتصاديَّة الدولية، يشكل جزءاً كبيراً من الدراسات النظريَّة ومن المعروف أنَّ جميع النظريات الوضعيَّة وخاصة الواقعيَّة بأشكالها المتعددة، تقدّم مادة علميَّة كبيرة في هذا المجال، ولقد حاولَ العديد من علماء و باحثين العلاقات الدوليّة من خلال الدراسات المختلفة والأبحاث المتعددة تحديد عوامل ومرتكزات تأثير هذه الوحدات في سلوك البعض، وتحديد الأسباب الكامنة وراء ذلك، وفي هذا البحث يحاول الباحث تحديد دور التكتلات الإقتصادية الدولية في التأثير على النظام الدولي، وبالتحديد تكتل البريكس التي في بداية عام 2011، بدأت تتحول من مجموعة اقتصاديّة دوليّة إلى مجموعة سياسية مؤثرة في السياسة العالميّة، حيث أنّ المواقف السياسيّة مرتبطة ارتباط تام بالصالح الاقتصادية، متمثلةً بالأعضاء الدائمين(روسيا والصين)، في مجلس الأمن. It noted a series of recent international events in the world that international relations have witnessed considerable turbulence, and revealed these events and developments that unilateral international system polar and who knew the world since the collapse of the Soviet Union, entered a period of vague political changes, and showed these developments and changes in the political, economic and military fields to the emergence of powers at the global level, represented by the international economic blocs are trying to influence the first circle of the international system and these conglomerates that have emerged on the international scene is the BRICS bloc. The controversy in the literature of international relations on the impact of the international system architecture in the behavior of actors in which units both State systems subsidiary and now the forces of an effective non-state such as international economic blocs, is a big part of theoretical studies it is known that all theories of positivism realism, especially in its many forms, progress big scientific material in this area, and we have many of the scientists and researchers of international relations through various studies and multiple research attempted to determine the factors and the pillars of the impact of these units in the behavior of the other, and to identify the reasons behind it, and in this research is to determine the role of economic blocs international in influencing the international system, specifically the bloc BRICS started at the beginning of 2011, began to turn from the international economic community to influential political group in the world politics, where political positions linked to fully link economic welfare, represented by permanent members (Russia and China), in the Security Council.